Effectiveness and organizational conditions of effectiveness of telemedicine in nursing homes. A study protocol of a comparative prospective cohort (EFFORT study). (January 2021) - Salles, Nathalie; Saillour-Glénisson, Florence; Sibe, Matthieu; Langlois, Emmanuel; Kret, Marion; Durrieu, Jessica; Arditi, Nora; Abraham, Maelys; Perry, Frederic
Introduction: The profile of nursing home (NH) residents has changed over the past decade with more dependency, more severe chronic diseases and more treatments prescribed. For residents, the major consequence is the higher risk of unplanned hospitalization. French guidelines recommend the development of interactive telemedicine (InT ) in NHs in order to improve access to care, and to decrease the rate of avoidable unplanned hospitalizations. Methods and analysis: The aim of this study is to analyze the impact of anInT protocol delivered in NHs on the rate of unplanned hospitalizations, and on the quality of life at work and the organizational conditions of effectiveness of telemedicine in NHs. We will perform a mixed methods study combining a cluster non-randomized controlled trial in two matched parallel arms (telemedicine group and control group) and qualitative analysis of the evolution of organizational and professional contexts in NHs. Ethics and dissemination: The study protocol was approved and sponsored by the French Ministry of Health. The study received ethical approval from the Bordeaux University Hospital Institutional Review Board. We will communicate the final results to the public via conferences and results will also be submitted for publication in international peer-reviewed scientific journals. Trial registration number NCT03486977